1996
DOI: 10.1515/mamm.1996.60.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Cetaceans of São Paulo, Southeastern Brazil

Abstract: OBJECTIVE: To assess the meaning of depression in women diagnosed with the disorder, and the context of care given by the psychiatrists who follow them up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Members of the temperate community are likely to be most common and extend further into the study area during the austral winter when the Benguela Current pushes furthest northwards. A similar situation occurs in the western Atlantic, where the transition between tropical and temperate cetacean communities occurs in São Paulo state, an area influenced by both the warm Brazil current and the cold Malvinas current (Martuscelli et al. 1996).…”
Section: Discussionmentioning
confidence: 72%
“…Members of the temperate community are likely to be most common and extend further into the study area during the austral winter when the Benguela Current pushes furthest northwards. A similar situation occurs in the western Atlantic, where the transition between tropical and temperate cetacean communities occurs in São Paulo state, an area influenced by both the warm Brazil current and the cold Malvinas current (Martuscelli et al. 1996).…”
Section: Discussionmentioning
confidence: 72%
“…Cetaceans' species included in this survey were: Family Balaenidae: Eubalaena australis , Family Balaenopteridae: Megaptera novaeangliae , Balaenoptera edeni and B. acutorostrata from the suborder Mysticeti and from the suborder Odontoceti, Family Delphinidae: Orcinus orca , Tursiops truncatus , Steno bredanensis , Stenella frontalis , Delphinus sp., Sotalia guianensis and Family Pontoporiidae: Pontoporia blainvillei . The distribution of these species along São Sebastião coast is heterogeneous, some of them occurring at the northern coast, others occurring at the southern coast and some have been recorded at the entire coast [43-46]. …”
Section: Methodsmentioning
confidence: 99%
“…Schmiegelow (1990) reports the stranding of two individuals on Comprida Island and at Marujá Beach (SP), both in October 1987. In addition, Martuscelli et al (1996) reported 14 strandings and one sighting between October 1985 and December 1994 at São Sebastião, Ubatuba, Grande and Peruíbe beaches, and Comprida, Cardoso and Castilho islands. A review of stranded bottlenose dolphins along the coast of SP indicated 40 previously unpublished records between August 1994 and January 2008 (Santos et al, 2010).…”
mentioning
confidence: 99%